Synthesis of industrially important platform chemicals via olefin metathesis of palash fatty acid methyl esters - Vyshnavi, Yelchuri; Prasad, Rachapudi Badari Narayana; Karuna, Mallampalli Sri Lakshmi (European Journal of Chemistry, 2014)
The study signifies the importance of olefin metathesis in developing industrially important platform chemicals from a non-edible renewable resource, palash oil using Grubb’s second generation catalyst. The reaction conditions were optimized by varying the concentration of the catalyst, 0.03-0.05 mM and the temperature, 45-100 °C of the reaction. Maximum yield of the metathesized products, as analysed using GC/GC-MS were obtained employing lower concentration of the catalyst, 0.03 Mm and temperature, 45 °C for 36 h. The metathesized products showed the formation of hydrocarbons namely 9-octadecene (10.9%) and cyclodecacyclotetradecene (27%) as major. The formation of cyclodecacyclotetradecene was observed for the first time. The study also describes the possible routes and the molecules involved in the formation of the metathesized products.